2017
DOI: 10.1088/1361-648x/aaa159
|View full text |Cite
|
Sign up to set email alerts
|

The effect of RNA stiffness on the self-assembly of virus particles

Abstract: Under many in vitro conditions, some small viruses spontaneously encapsidate a single stranded (ss) RNA into a protein shell called the capsid. While viral RNAs are found to be compact and highly branched because of long distance base-pairing between nucleotides, recent experiments reveal that in a head-to-head competition between a ssRNA with no secondary or higher order structure and a viral RNA, the capsid proteins preferentially encapsulate the linear polymer! In this paper, we study the impact of genome s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…The latter, which is very flexible, might then collapse through a coil–globule transition that could allow the bound subunits to contact each other and to build up a closed shell, despite the energy barrier related to their electrostatic repulsion and to the conformational change required to arrange onto an icosahedral lattice. A recent theoretical study demonstrated that flexible, linear chains require less free energy than stiff, branched ones to be confined in a capsid 47 , which is in qualitative agreement with our results. Like virions, PSS-filled capsids are stable against dilution, which indicates that, at the end of assembly, the subunits making up the capsid are no longer able to exchange with the bulk solution.…”
Section: Resultssupporting
confidence: 92%
“…The latter, which is very flexible, might then collapse through a coil–globule transition that could allow the bound subunits to contact each other and to build up a closed shell, despite the energy barrier related to their electrostatic repulsion and to the conformational change required to arrange onto an icosahedral lattice. A recent theoretical study demonstrated that flexible, linear chains require less free energy than stiff, branched ones to be confined in a capsid 47 , which is in qualitative agreement with our results. Like virions, PSS-filled capsids are stable against dilution, which indicates that, at the end of assembly, the subunits making up the capsid are no longer able to exchange with the bulk solution.…”
Section: Resultssupporting
confidence: 92%
“…An important aspect of virus assembly in the presence of genomic RNA is the need for genome compaction [ 10 ], and several groups have made important contributions to the modelling of this aspect of virus assembly [ 11 • , 12 , 13 • , 14 • ]. The impact of non-specific electrostatic interactions between genomic RNAs and CP [ 15 , 16 , 17 , 18 , 19 •• ] and of the stiffness of the RNA molecule on the assembly process [ 20 • ] have been analysed. It has also been shown that the secondary structure of the RNA molecules play an essential role in determining capsid morphology in the self-assembly of Cowpea Chlorotic Mottle Virus (CCMV)-like particles [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also explain this effect by the hydrophobic properties of PSS, which is poorly soluble in water and exists in a collapsed form [ 24 ]. Moreover, they noted that linear, flexible PSS chains require less free energy to be encapsulated than particles with stiff conformations, such as RNA [ 24 , 30 ].…”
Section: Discussionmentioning
confidence: 99%